Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan - Aditya, Made Purwa; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen; Vol 6 No 9 (2017), 2017)
The purpose of this study is to explain the role of customer satisfaction mediate the influence of Service Quality on customer loyalty at MyBali Tour company. This research was conducted at service company MyBali Tour in Denpasar-Bali City. The number of samples taken as many as 100 respondents who are customers of MyBali Tour services, by sampling method. The data were collected through questionnaires and interviews. Analytical technique used is path analysis. Based on the analysis result found that service quality variable have positive and significant influence to customer loyalty in MyBali Tour company, service quality variable have positive and significant influence to customer satisfaction at MyBali Tour company, customer satisfaction variable have positive and significant influence to customer loyalty at MyBali Tour company, and customer satisfaction variables have a positive and significant impact on service quality and customer loyalty in MyBali Tour company.